Trends in the prevalence of non-standard employment in Australia - Lass, Inga; Wooden, Mark (My University, 2020)
This article provides an overview of the measurement of, and trends in, the prevalence of non-standard employment in Australia. Using the most recent data from the Household, Income and Labour Dynamics in Australia Survey (2001–2017), the share of non-standard employment in total employment is estimated to have been 54.9% in 2001. In the most recent data (for 2017) the share is only slightly higher – 55.6%. Still, the intervening period was marked by significant changes, with the share of nonstandard workers declining until 2008, and increasing again since then. Within the broad group of non-standard employment, the prevalence of individual employment types has developed in different directions. While casual employment has followed the overall trend of an initial decline followed by a recent increase, the shares of permanent parttime work and fixed-term contracts in total employment have increased throughout most of the period, and the reverse is true of self-employment. These trends can only to a limited degree be explained by changes in worker and job characteristics, leading to the conclusion that these changes are primarily due to changed job selection behaviour of workers and/or changed hiring practices of employers.
Journal of Industrial Relations
Keywords: Labour market